Le souterrain médiéval de Chauviat (commune de Charbonnières-les-Vieilles, Puy-de-Dôme) - Frédéric Surmely; Patrick Boudon; Stéphane Guyot; Pierre Caillat; Pierre Charbonnier; Laurent Hablot; Thomas Poiraud (Revue Archéologique du Centre de la France)
As some work had been carried out by a farmer, we were able to make a close and thorough inspection of a medieval tunnel in the Combrailles area. The forty-metre long gallery had three entrances and special draining facilities for water seepage. The gallery was then used as a garbage dump and test excavations have yielded abundant archeological material: broken ceramics, fauna, an iron stirrup, an arrowhead and a very unexpected papal bull of Martin IV (1281-1285). The structure was linked to an aristocratic home still to be excavated. It was probably an escape tunnel different from the common tunnels destined to the storage or the refuge. It is rather difficult to date precisely when it was built, but it was very likely at the end of the 13th century.